Factors describing community ambulation after stroke: a mixed-methods study. (May 2015) - Barclay, Ruth; Ripat, Jacquie; Mayo, Nancy
Objective: To develop a model of community ambulation after stroke based on: Canadian data from community-dwelling individuals post-stroke; the experiences and opportunities for community ambulation expressed by individuals with stroke; and current literature. The model presents a visual depiction of the relationships between the different factors of community ambulation after stroke. Design: A quantitative/qualitative explanatory sequential mixed-methods design was utilized. Secondary data analysis with structural equation modeling resulted in a community ambulation model. Two focus groups of individuals with stroke were conducted to verify and explain the model. Setting: Community. Subjects: Quantitative data from 227 participants: 142 (63%) male; 63.4 (12.0) years of age and 2.6 (2.5) years post stroke. Eleven individuals participated in the focus groups: 6 (55%) male; 61.4 (6.9) years of age and 5.8 (3.3) years since stroke. Main measures: Model variables: items from the EuroQol, Preference Based Stroke Index, gait speed, Reintegration to Normal Living Index, the Community Health Activities Model Program for Seniors, and the Geriatric Depression Scale. Results: The model had reasonable fit with three latent variables: ambulation, gait speed, and health perceptions (normed χ 2 = 1.8, root mean square error of approximation = 0.060 (0.043; 0.075)). Depression was also a component of community ambulation. Participants verified the model and added endurance and the environment as additional components. Participants used self-awareness and knowledge of the environment to engage in cognitive strategies related to community ambulation. Conclusions: A model of community ambulation after stroke was developed and verified. Recognizing important components of community ambulation may assist physiotherapists in determining community ambulation goals, needs, and opportunities in partnership with clients.